A Comprehensive Methodology for Estimating Yearly Plastic Pollution Loads in Rivers - Stephanie B. Oswald; Esmee S. Oldenhof; Ad M. J. Ragas; Margriet M. Schoor; Frank P. L. Collas (Water, Air, & Soil Pollution, 2026)
Plastic pollution in freshwater systems represents a major global concern, as rivers serve as critical pathways between land-based sources and marine environments. Yet, inconsistencies are observed between estimated plastic inputs from land and concentrations in the ocean. Despite growing monitoring efforts, the lack of standardized methods and the use of diverse metrics for quantifying plastic pollution hamper direct comparisons across studies and limit comprehensive assessments. In this study, we developed a method for quantifying yearly macro- and mesoplastic load, incorporating different metrics. By integrating statistical analysis, the method accounts for variability in plastic concentrations and discharge rates. Subsequently, this methodology was applied to the Rhine and Meuse rivers in the Netherlands. The findings of this study indicate a spatial variability in plastic concentrations. The mean annual load of macro- and mesoplastics (items > 0.5 cm) in the Rhine was highest at Lobith, located at the Germany–Netherlands border (331 million items/year), decreasing downstream to 206 million items/year at Tiel. Similarly, in the Meuse, higher loads were observed at Eijsden, at the Belgium–Netherlands border (73 million items/year), than further downstream at Sambeek (62 million items/year), while particles in the 5–6 mm size range are likely underrepresented due to the 6 mm mesh size of the sampling net. Correspondingly, the mean annual surface area load of macro- and mesoplastics in the Meuse showed a downstream decrease, with mean values declining from 71,641.63 m 2 /year at Eijsden to 30,714.92 m 2 /year at Sambeek. The methodological approach enables the quantification of plastic loads, providing important insights into the dynamics of plastic pollution in river systems. This allows for predictions of future plastic quantities in the Rhine-Waal and Meuse rivers under different emission scenarios and measurement units.

Biotechnological adsorbents for removal of drugs from water: use of microorganisms, biopolymers, and composite materials - G. Marchezi; G. Concolato; L. M. Colla; J. S. Piccin (International Journal of Environmental Science and Technology, 2026)
Emerging contaminants pose significant risks to environmental and human health, warranting detailed investigation. Among these contaminants, pharmaceuticals and their metabolites are of particular concern, as they are widely released into the ecosystem. Their chemical and biological stability contributes to their persistence in aquatic systems and limits the effectiveness of conventional water treatment technologies. Adsorption is one of the most commonly used advanced treatment techniques for removing pharmaceuticals due to its favorable operation and cost-effectiveness. The use of adsorbents obtained through biotechnological processes has emerged as a promising approach due to their efficiency and environmental sustainability. Promising biotechnological adsorbents include live microorganisms such as fungi, bacteria, and microalgae. Dead or inactive biomass also shows applicability, being considered lower in cost. Additionally, algae and adsorbents based on natural polymers obtained through biotechnological processes, such as sodium alginate, bacterial cellulose, and chitosan, stand out. Biocomposites enable the combination of desirable characteristics from more than one material, resulting in adsorbents with better performance and lower environmental impact compared to conventional alternatives. Moreover, adsorption processes employing biocomposites often operate under mild conditions, such as neutral pH and ambient temperature, further increasing their applicability. Thus, this literature review aims to explore the application of adsorption processes for the removal of pharmaceuticals from water using adsorbents derived from biotechnological processes.

Development of biochar-immobilized Bacillus subtilis BEIB-18 for hexavalent chromium (Cr(VI)) bioremediation in aqueous medium - V. A. Schommer; M. T. Nazari; A. P. Vanin; D. D. C. Krein; N. Melo; L. F. dos Santos; G. L. Dotto; V. Ferrari; L. M. Colla; A. Dettmer; J. S. Piccin (International Journal of Environmental Science and Technology, 2026)

Evaluation of riverine macro- and mesoplastic monitoring approaches - Stephanie B. Oswald; Paul Vriend; Ad M. J. Ragas; Margriet M. Schoor; Frank P. L. Collas (Environmental Monitoring and Assessment, 2026)
Globally, plastic pollution in aquatic environments has become an emerging concern. A multitude of monitoring techniques have been used to collect information on the presence of macroplastics (> 25 mm) and mesoplastics (> 5 mm ≤ 25 mm) in river systems. The differences between these methodological approaches, combined with limited knowledge of the fundamental processes that affect plastic presence and detection ability, lead to a lack of standardization between methods and limit comparisons of quantitative data on plastic pollution among studies. This study investigates how different monitoring approaches, e.g., larvae net, trawl net, and stow net, affect the observed abundance and composition of macro- and mesoplastics in the Rhine-Waal Rivers. Additionally, we performed a SWOT analysis highlighting the strengths, weaknesses, opportunities, and threats of the three methods. During trawl net and stow net monitoring, more unique macro- and mesoplastics categories were found in comparison with simultaneous larvae net monitoring. However, while mean macroplastic concentrations were higher in the stow net samples (1.22 × 10 –3 items/m 3 ) than in the larvae net (0.91 × 10 –3 items/m 3 ), mesoplastics concentrations were significantly higher in the larvae net samples (6.91 × 10 –3 items/m 3 ) compared to those recorded with the stow net (1.15 × 10 –3 items/m 3 ), indicating that the size plastic recovery rates depend on the sampling technique. The SWOT analysis pointed towards a better overall performance of the trawl net. The outcome of the current study can be used to support policymakers, industry, and the scientific community in developing successful monitoring strategies for macro- and mesoplastics pollution in rivers. The SWOT analysis may facilitate the choice of the approach that best aligns with the specific monitoring goals and the environmental conditions of the target area.

Energy and nutrient recovery from anaerobic co-digestion of malting wastewater and microalgae biomass - A. Rubert; C. Kaminski; M. T. Nazari; D. D. C. Krein; L. M. Colla; J. A. V. Costa; M. Hemkemeier (International Journal of Environmental Science and Technology, 2025)

Exploring ecosystem‐based management in the North Atlantic - Mark Dickey‐Collas; Jason S. Link; Paul Snelgrove; J. Murray Roberts; M. Robin Anderson; Ellen Kenchington; Alida Bundy; Margaret M. (Peg) Brady; Rebecca L. Shuford; Howard Townsend; Anna Rindorf; Murray A. Rudd; et al. (Journal of Fish Biology, 2022)
The United States, the EU and Canada established a trilateral working group on the ecosystem approach to ocean health and stressors under the Atlantic Ocean Research Alliance. Recognizing the Atlantic Ocean as a shared resource and responsibility, the working group sought to advance understanding of the Atlantic Ocean and its dynamic systems to improve ocean health, enhance ocean stewardship and promote the sustainable use and management of its resources. This included consideration of multiple ocean‐use sectors such as fishing, shipping, tourism and offshore energy. The working group met for 4 years and worked through eight steps that covered the development of common language as a basis for collaboration, challenges of stakeholder engagement, review of the governance mandates, exploring the links between sectors and ecosystems effects, identifying gaps in knowledge and uptake of science, identification of tools for ecosystem‐based management, customary best practice for tool development and communication of key research priorities. The key findings were that ecosystem‐based management enables new benefits and opportunities, and that we need to make the business case. Further findings were that adequate mandates and effective tools exist for ecosystem‐based management, and that ecosystem‐based management urgently requires integration of human dimensions, so we must diversify the conversation. In addition, it was found that stakeholders do not see their stake in ecosystem‐based management, so greater engagement with stakeholders and targeting of ocean literacy is required and a sustainable future requires a sustained investment in ecosystem‐based management, so long‐term commitment is key.

Assessing Habitat Suitability for Native and Alien Freshwater Mussels in the River Waal (the Netherlands), Using Hydroacoustics and Species Sensitivity Distributions - N. Y. Flores; F. P. L. Collas; K. Mehler; M. M. Schoor; C. K. Feld; R. S. E. W. Leuven (Environmental Modeling & Assessment, 2022)
Longitudinal training dams (LTDs) in the river Waal are novel river training structures that protect the littoral zone from the adverse effects of navigation providing new habitats for riverine macroinvertebrates. In order to inform river management and to better understand their ecological value for native and alien mussel species, it is important to assess the habitat suitability of the protected LTD shore channels. We applied spatial hydroacoustics surveys consisting of side-scan sonar (SSS) and acoustic Doppler current profiler (ADCP) of the substrate type, water depth and flow velocity in three shore channels in combination with species sensitivity distributions (SSDs) to predict habitat suitability for native and alien mussel species. SSDs allowed for the prediction of habitat suitability as a potentially occurring fraction (POF) of a species pool. High substrate type, water depth, and near-bottom flow velocity POFs were found for ≥ 70%, 100%, and 4–51% of the total shore channel area, respectively, suggesting that shore channels provide suitable habitat for both native and alien mussel species. To enhance the shore channels as habitat for native mussel species, we recommend increasing shallow areas dominated by fine (silt/clay) and sand substrate types with low near-bottom flow velocities (near 0 m/s). In contrast, the total area of hard substrate (e.g., boulders) in the shore channels should be reduced as it strongly favored invasive alien mussel species in our study. Future research should include additional abiotic parameters to enhance the habitat suitability predictions and compare the results for different riverine habitats.

Microalgae consortia cultivation using effluents for bioproduct manufacture - F. G. Magro; J. F. Freitag; A. Bergoli; V. A. F. Cavanhi; L. M. Colla (Reviews in Environmental Science and Bio/Technology, 2021)

Extracellular biosurfactants from yeast and soil–biodiesel interactions during bioremediation - N. E. Kreling; M. Zaparoli; A. C. Margarites; M. T. Friedrich; A. Thomé; L. M. Colla (International Journal of Environmental Science and Technology, 2020)

National contributions to global ecosystem values - Laura E. Coristine; Sheila Colla; Nathan Bennett; Anja M. Carlsson; Christina Davy; Kimberley T.A. Davies; Brett Favaro; D.T. Tyler Flockhart; Kevin Fraser; Diane Orihel; Sarah P. Otto; Wendy Palen; et al. (Conservation Biology, 2019)
Current conservation templates prioritize biogeographic regions with high intensity ecosystem values, such as exceptional species richness or threat. Intensity‐based targets are an important consideration in global efforts, but they do not capture all available opportunities to conserve ecosystem values, including those that accrue in low intensity over large areas. We assess six globally‐significant ecosystem values—intact wilderness, freshwater availability, productive marine environments, breeding habitat for migratory wildlife, soil carbon storage, and latitudinal potential for range shift in the face of climate change—to highlight opportunities for high‐impact broadly‐distributed contributions to global conservation. Nations can serve as a cohesive block of policy that can profoundly influence conservation outcomes. Contributions to global ecosystem values that exceed what is predicted by a nation's area alone, can give rise to countries with the capacity to act as ‘conservation superpowers’, such as Canada and Russia. For these conservation superpowers, a relatively small number of national policies can have environmental repercussions for the rest of the world.

MPP+-Lesioned Mice: an Experimental Model of Motor, Emotional, Memory/Learning, and Striatal Neurochemical Dysfunctions - Mauricio P. Cunha; Francis L. Pazini; Vicente Lieberknecht; Josiane Budni; Ágatha Oliveira; Júlia M. Rosa; Gianni Mancini; Leidiane Mazzardo; André R. Colla; Marina C. Leite; Adair R. S. Santos; Daniel F. Martins; et al. (Molecular Neurobiology, 2017)

Creatine Prevents Corticosterone-Induced Reduction in Hippocampal Proliferation and Differentiation: Possible Implication for Its Antidepressant Effect - Francis L. Pazini; Mauricio P. Cunha; Dayane Azevedo; Julia M. Rosa; André Colla; Jade de Oliveira; Ana B. Ramos-Hryb; Patricia S. Brocardo; Joana Gil-Mohapel; Ana Lúcia S. Rodrigues (Molecular Neurobiology, 2017)

Creatine, Similar to Ketamine, Counteracts Depressive-Like Behavior Induced by Corticosterone via PI3K/Akt/mTOR Pathway - Francis L. Pazini; Mauricio P. Cunha; Julia M. Rosa; André R. S. Colla; Vicente Lieberknecht; Ágatha Oliveira; Ana Lúcia S. Rodrigues (Molecular Neurobiology, 2016)

A review and critical analysis of the European situation of soilborne disease management in the vegetable sector - P. Colla; G. Gilardi; M. L. Gullino (Phytoparasitica, 2012)

Does the western Irish Sea gyre influence the distribution of pelagic juvenile fish? - M. Dickey‐Collas; J. Brown; L. Fernand; A. E. Hill; K. J. Horsburgh; R. W. Garvine (Journal of Fish Biology, 1997)
The western Irish Sea is an important spawning and nursery ground for many commercially exploited fish. Spawning begins in the Irish coastal regions in early spring, and moves offshore as the season develops. As a result of the onset of seasonal heating in spring, stratification isolates a dome of cold bottom winter water in the deep (>100 m) basin of the western Irish Sea. The resultant density fields drive a cyclonic gyre which dominates the circulation of the region during late spring and summer and is characterized by anticlockwise current speeds which exceed 0.2 ms –1 , after removal of tides. Surveys of pelagic juvenile (0‐group) fish in 1994, 1995 and 1996, showed that they were coincident with the centre of the gyre. Physical data from 1994 and 1995, were used to describe the horizontal and vertical structure of the water column and the associated circulation regime. The behaviour and swimming speeds of pelagic juvenile fish were insufficient to explain their apparent shift in abundance away from the coast to the central western Irish Sea. Drifter and current data suggested that their entrainment into the gyre could provide both the transport and retention mechanisms.